Does Corporate Social Responsibility Moderate the Effect of Information Asymmetry and Earnings Management on Cost of Equity Capital? - Urna Fasihat, Dian; Iskandar, Rizkiana (International Journal of Science, Technology & Management, 2024)
This study explores the relationship between information asymmetry, earnings management, Corporate Social Responsibility (CSR), and cost of equity capital (CEC). The results show that information asymmetry has a significant influence on CEC, which indicates that information uncertainty can increase the cost of equity capital of a company. On the other hand, earnings management practices have not been shown to have an effect on CECs, reflecting that investors may be more focused on long-term performance than short-term financial statement manipulation. In addition, CSR cannot moderate the influence of information asymmetry on CEC or the influence of earnings management on CEC.